The relationship between leadership styles of estate managers and organizational performance of oil palm estates in Tawau Sabah - Sappe@Sophia Osman (2014)
The relationship between leadership styles of estate managers and organizational performance of oil palm estates in Tawau, Sabah has conducted in this study. This study also has identify the leadership style of estate managers that implemented in area conducted and the effect with the organizational performance measured by employees performance in terms of executive and non executive levels. During this studied, two hundred five (205) respondents has participated to answer the questionnaire that distributed. The respondents answer was collected from eleven (11) estates and with different background of demographic. Majority of the respondent's gender is male with 92.2% from the total percentage of the respondents. In the other hands, the respondents aged within 21 years old to 30 years with experience majority range within 2 years to 5 years working experience. The data collected analyses with SPSS 20 version to find the statistical results. From the result analyses, it found that in performance factor one (1) the leadership style that has accepted in oil palm estate is laissez-faire dimension from Passive/Avoidant Leadership style (p=0.047,0=0.144) and for performance factor two (2) dimension accepted is idealized influence (p=0.033,0=0.163) from Transformational Leadership and management by exception - active (p=0.033,0=0.177) from Transactional Leadership style. Besides that, suitable leadership style in order to achieve work performance, t value is the very best to explain the level to gain in the long term success.